النظام الضريبي وأثره في الحد من التلوث البيئي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
توضح هذه الدراسة عمق وأبعاد مشكلة التلوث البيئي التي تمثل ظاهرة عالمية لها أبعادها الخطيرة ، وهي محور الاهتمام في مطلع هذا القرن ، نظراً لتداعياتها الخطيرة وِآثارها على خطط التنمية الاقتصادية والاجتماعية وعلى رفاهية المجتمع. وتعرض هذه الدراسة أدوات النظام الضريبي ( المباشرة وغير المباشرة ) التي يمكن استخدامها لمواجهة التلوث البيئي، حيث تم مناقشة الضريبة على المنتجات والانبعاثات بالإضافة إلى مجموعة أخرى من الأدوات غير المباشرة كنظام الودائع والتأمينات الإرجاعية ونظام تصاريح التلوث القابلة للتداول. ثم تناولت الدراسة مشاكل وصعوبات تطبيق ضرائب التلوث كصعوبة تحديد المستوى المعياري للتلوث وتقدير التكاليف الخارجية للتلوث البيئي وانخفاض الوعي البيئي ........ وصولاً إلى بعض النتائج والتوصيات التي تستهدف توضيح أهمية الإسراع في تطبيق نظام ضريبي جديد. This study reflects the effect of the environment, which is a world's phenomena, having its serious consequences on economic plans and social welfare. The study reviews the tools of the taxation policies (direct and indirect tools) that can be employed in addition to confronting the environment pollution, for it discusses the taxes imposed on emissions and on outputs, besides other sets of indirect tools like deposits-refund systems and trade permits pollution. This study discusses the problems and difficulties that are associated with the application of pollution taxes like the difficulty in determining the standards of pollution and the external expenses and costs of pollution in environment, along with the internal conciseness reduction. The study reaches some conclusions and provides some recommendations to clarify the importance of speeding up plans for the application of a new taxation system.